PENGUATAN TUJUAN PENDIDIKAN NASIONAL MELALUI ASMAULHUSNA - WAHIDIN, ADE (Jurnal Pendidikan Islam, 2018)
Ideally the purpose of every educational activity, both formal and non formal is formulated first, particularly in the national level. As a Muslim majority country, Indonesia formally decide its national educational goals that leads to the establishment of faithful, pious, and noble people. Among the ways that every Muslim can utilize to strengthen the goals of national education is through referring to Asmaul-Husna as the basis for the formation of faith, piety, and noble character in everyday life. Therefore, this study discusses about how a Muslim implemented his national educational goals with Asmaul-Husna.